IMPLEMENTING PREDICT OBSERVE EXPLAIN (POE) STRATEGY TO TEACH READING EXPOSITION TEXT - Ratna Nery; Fitri Novia (Universitas Muhammadiyah Metro, 2022)
The purpose of this study was to investigate if POE (Predict, Observe, Explain) strategy influenced students' reading ability when reading an exposition text. This study was conducted using an experimental design. Purposive sampling was used to select the sample. The sample consisted of 42 students. The research instrument was a multiple-choice test with 40 questions about the exposition text. A t-test was used to analyze the data. Based on the independent sample t-test, the value of t- obtained was -6.793 at significance level p<0.005 in the two-tailed testing and df=40, the critical value of t-table was 2.0210. Since the value of t-obtain (-6.793) was higher than t-table (2.0210) and p-value (0.00) was less than the α value (0.05), it meant that Predict, Observe, Explain strategy helped students learn quickly to understand the content of the text.